If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4r + 5) + 7 = 58 Reorder the terms: 3(5 + 4r) + 7 = 58 (5 * 3 + 4r * 3) + 7 = 58 (15 + 12r) + 7 = 58 Reorder the terms: 15 + 7 + 12r = 58 Combine like terms: 15 + 7 = 22 22 + 12r = 58 Solving 22 + 12r = 58 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 12r = 58 + -22 Combine like terms: 22 + -22 = 0 0 + 12r = 58 + -22 12r = 58 + -22 Combine like terms: 58 + -22 = 36 12r = 36 Divide each side by '12'. r = 3 Simplifying r = 3
| 3p+15=30 | | (2x+1)=56-(2x+1) | | 37x^2-3x+88=0 | | 55-x+28=17 | | x+2y+2z=70 | | 16x-3=9+5x | | x+2x=2x+30 | | 5m-(6w+9)=11 | | 7-3x=5x+19 | | 5p-7=4p+3 | | 4m-5=6m+d | | (2x+1)+y=56 | | 16-3p=-21 | | 110+(3x-20)=180 | | 4x+12+34=180 | | 9x-8y=16 | | x^3-5x^2+2x+10=0 | | x^3-5x+2x^2+10=0 | | x^3-15=39 | | 12+x-x^2= | | 20-x-x^2= | | 14-5x-x^2= | | 9(x-4)+2(1+4x)=0 | | 12+4x-x^2= | | 2a-10=-8 | | 5-4x-x^2= | | -5(-3-x)-12=3(1+11x) | | 4x+7=6x-2 | | -11+8x=5x+7 | | 2x-45=15 | | -4x+-3(x-5)=8x | | 8+2x-x^2= |